LIVING QUR’AN RESEARCH METHOD - Adi, Habib Maulana Maslahul; ., Muhsin; Zarkasyi, Mohammad Fikri; Mufidah, Afifah Ikram (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to analyze the application of triangulation as a method for testing data validity in Living Qur’an research within student papers. This research employs a qualitative approach, which, in terms of its background, falls under library research. Data were obtained from the repository of students’ final assignments at PTIQ Jakarta University as the research sample. Data collection was conducted using documentation techniques, followed by content analysis. Based on the research findings, it is concluded that only a small portion of student papers related to the Living Qur’an explicitly mention triangulation as part of their data validation process. However, triangulation techniques have been implicitly applied in student research. The types of triangulation used mainly include methodological triangulation and source triangulation. Nevertheless, inconsistencies in its application have been observed, which may raise doubts about data validity and lead to premature conclusions. Apart from these two types, time triangulation and theoretical triangulation have not been widely utilized and, in fact, tend to be entirely absent.